USING MIXIDEA ONLINE DEBATING STRATEGY TO PROMOTE THE STUDENTS’ SPEAKING ABILITY - Aulia Sari; Aswadi Jaya; Hermansyah Hermansyah; Asti Veto Mortini (Universitas PGRI Palembang, 2022)
The problem of the study was there any significant difference between the Tenth Grade students of SMA Dharma Bhakti Palembang who were taught trough Mixidea Online Debating Strategy and those who were not. Therefore, the objective of the study was to find out whether or not there is any significant different scores between Tenth Grade students of SMA Dharma Bhakti Palembang who are taught through Mixidea Online Debating Strategy and those who are not. Quasi Experimental research design was applied in this study. The population of this study was 68 of Tenth Grade students of SMA Dharma Bhakti Palembang. The sample was selected by using purposive sampling method non-random sampling. Oral test was used as technique in collecting the data and they were analyzed by using independent sample t-test. From this study, the writer found out that Mixidea Online Debating Strategy was effective to be taught to the Tenth Grade Students of Dharma Bhakti Palembang. It could be seen from the result of t-obtain (22.585) was higher that t-table (4.290) where 34 students based on the table stated. Besides the null hypothesis (Ho) was rejected and alternative hypothesis was accepted.